CARACTERÍSTICAS DA LOCALIZAÇÃO NO PROCESSO DE INTERNACIONALIZAÇÃO DE EMPRESAS - Érica Piros Kovacs; Walter Fernando Araújo de Moraes; Brigitte Renata Bezerra de Oliveira (RAE: Revista de Administração de Empresas, 2011)
This paper aims to analyze what extent the location influences the internationalization process of Brazilian companies. From fivemodels of internationalization, that key concept is cross compared to explain the empirical analysis of the cases. The research is characterized by its longitudinal approach and methodological procedures based on the adaptive theory. Data analysis was performed in two stages: descriptive and the method of constant comparison, both using ATLAS/ti software. Based on the concept properties, four significant events emerged, with distinct dominance over time: trends, and comparative locational advantages (transactional and comparative) and disadvantages. The results show thatthe comparative advantages were decisive for the start of the internationalization and boosted the trends in the region. Transactional benefits are present in later stages, acquired through the opening of subsidiaries abroad. Locational disadvantages were also perceived throughout the whole process due to unforeseen chance events